Passivo ambiental em propriedades rurais: Ilha das Flores - Porto Alegre - RS - Sampaio, Marcela Vilar (2006)
The acceleration of the global economy and shifting demographic changes has caused an uncontrolled exploration of the worlds natural renewable and non-renewable resources. Not only have the levels of these resources decreased but so has the quality. In addition to these changes, the future development of natural ecosystems could also be compromised as they are finite. In order to establish a harmonious equilibrium between population, economic growth and natural resources, emerged the necessity of appraising under the view of the environmental economy, the economie value of environmental profits.Studies and techniques have been designed to help us understand such relationships. One model is known as the environmental Passive. This one is defined as group of real or potential debts that the man, the company or the property possesses with the nature for being in disconformity with relationship the legislation or proposed environmental procedures. The objective of evaluating and to quantifying the impacts that man is causing to the nature is to make that the value found be used to compensate the negative impacts. This study intended to develop a methodology which would be technical, scientific, useful and effective for quantification environmental passives in rural properties and, through the determination of the degree of deterioration of the Rural Property corresponding to the Micro basin, using the matrix of Leopold-Rocha methodology (2002); calculate the environmental passive as the result of the human actions that occured in a propertie in the Flowers Island - Porto Alegre - RS, applying the proposal methodology in this propriety grouping analisys of the achieved values in the environmental impact assessement, by WARD Method, using the statistic SAS SYSTEM 8.2, and do the cmparsion of the values obtained in the environmental passive. The real deterioration degree obtained by the Leopold-Rocha matrix reach 7,95%, this values demand urgent mitigation and compensatory mesures, for this percentage decrease, known that for rates under 10%, the environment is capable to recover. The price calculate of the Environmental Passive is R$ 81.606,72. In grouping analisys by the WARD method as resoult 2 distinct groups (A e B). The group A is compose by: Modification of the Regime and Transformation of the territory and construction with magnitude average (4,92%) e importance (8,45%), this is the group with more influent impacts. The environemental factors were separated in 3 distintc groups (A, B e C). The group A, Factors, present a magnitude (2,34%) and importance (3,76%), that values are the most higth, then this factor is suffer more impact than the outhers. In comparison the deterioration values of the environmental impact, the grouping analisys and the Passive, it may say that the actions with more impact were the one which had the high value of calculated Passive. Therefore this value should be used to revert caused impacts.